Competitive vs cumulative approach in teaching macroeconomics: Some thoughts on recent popular textbooks - Emilio Carnevali (PSL Quarterly Review, 2022)
This paper critically evaluates two different approaches to teaching macroeconomics at the undergraduate level through the comparison of two popular, recent handbooks: Olivier Blanchard's Macroeconomics (2021) and William Mitchell, Randall Wray and Martin Watts's Macroeconomics (2019). These textbooks are taken as benchmarks of two opposite views of the discipline: the cumulative - that is, followed by Blanchard and most "mainstream" textbooks - as opposed to the competitive view.
Keywords: A2; A22; E5; E12; 330; Teaching of economics; monetary policy; IS-LM model